PENDUGAAN PENCEMARAN AIR TANAH DI TEMPAT PEMBUANGAN SAMPAH LANDASAN ULIN TIMUR DENGAN METODE GEOLISTRIK KONFIGURASI SCHLUMBERGER - Denok Dwi Priyanti; Sri Cahyo Wahyono; Simon Sadok Siregar (Jurnal Fisika FLUX, 2014)
ABSTRACT. Along with the increment of human population, ground water pollution also tends to increase. It primarily due to the accumulation of waste which could harm the public health. Trash or waste is one of the important issues which could contaminate ground water, especially waste landfills. Ground water that has been contaminated with liquid waste (leachate) can affect the quality of ground water. This study aimed to determine the composition of rocks, layers and depth of ground water around waste landfills (TPS) and to determine whether ground water around the TPS is contaminated or not. Estimation of groundwater pollution could be determined by measurement using geoelectric method with schlumberger configuration. It showed  the presence of leachate layer at depth of 0,51 – 8,51 m with measured resistivity of 3,89 – 9,63 Ohm.meter, while groundwater is at depth of 22,92 – 26,59 m with resistivity value of 88,98 – 128,75 Ohm.meter. AAS sample test has been conducted to determine whether the ground water around TPS is contaminated or not.  The test results using AAS showed groundwater around TPS was contaminated with Lead (Pb), iron (Fe) and Cadmium (Cd). The evidence was the value of their concentrations in three water samples which exceeded the thresholds in accordance with the requirements of drinking water. Threshold for Pb, Fe and Cd are 0,01 ppm, 0,3 ppm and 0,003 ppm, respectively. From the measurement results of sample 1, 2 and 3 couls be obtained the concentration of  Pb are 0,084 ppm, 0,044 ppm and 0,091 ppm, the concentration of Fe are 0,812 ppm for 1,018 ppm and 0,203 ppm, while the concentration of Cd are 0,012 ppm, 0,017 ppm and 0,01 ppm. Keywords: Ground water, waste, geoelectric, AAS